2023
DOI: 10.1097/nna.0000000000001361
|View full text |Cite
|
Sign up to set email alerts
|

Violent Event Severity Tool for Reporting Violent Incidents

Son Chae Kim,
Youngho Paul Kim

Abstract: OBJECTIVES To explore the usefulness of the Violent Event Severity Tool (VEST). BACKGROUND The Joint Commission and many governing bodies require establishing workplace violence prevention programs in hospitals. Inconsistent processes have hampered the efficacy evaluation of such programs for collecting and reporting violence. The VEST was developed as a standardized tool for capturing violence data. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This violent event rate is consistent with previous studies that reported rates of 1.2% or 1.7%. 8 , 27 These low percentages of ED patients exhibiting violent behaviors appear to conflict with the high percentages of ED staff experiencing violence. However, the percentages are based on two different units of measure: the former is based on every 100 ED patients, whereas the latter is based on every 100 ED staff.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This violent event rate is consistent with previous studies that reported rates of 1.2% or 1.7%. 8 , 27 These low percentages of ED patients exhibiting violent behaviors appear to conflict with the high percentages of ED staff experiencing violence. However, the percentages are based on two different units of measure: the former is based on every 100 ED patients, whereas the latter is based on every 100 ED staff.…”
Section: Discussionmentioning
confidence: 99%
“…The VEST was used to collect data on various types and severities of violence. 8 The VEST provides operational definitions of six violence types, including physical assault, physical threat, verbal threat, verbal abuse, sexual harassment, and written threat. Each violence type includes severity criteria ranging from grade 1 (mild) to grade 4 (life threatening) to objectively capture the events.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation